The association between various visual function tests and low fragility hip fractures among the elderly: A Malaysian experience - Chew, Fiona L. M.; Yong, C.K.; Ayu, S.M.; Tajunisah, I. (Oxford University Press, 2010)
Objective: to determine the association between various visual function tests and low fragility hip fractures in an Asian population. Design: case-control study. Setting: University Malaya Medical Centre, Kuala Lumpur, Malaysia. Subjects: 108 cases aged >= 55 years admitted with low fragility fractures and 108 controls (matched for age, gender and race). Methods: both cases and controls underwent a detailed ophthalmological examination, which included visual acuity, stereopsis, contrast sensitivity and visual field testing. Results: poorer visual acuity (odds ratio, OR = 4.08; 95% confidence interval, CI: 1.44, 11.51), stereopsis (OR = 3.60, 95% CI: 1.55, 8.38), contrast sensitivity (OR = 3.34, 95% CI: 1.48, 7.57) and visual field defects (OR = 11.60, 95% CI: 5.21, 25.81) increased the risk of fracture. Increased falls were associated with poorer visual acuity (OR = 2.30, 95% CI: 1.04, 5.13), stereopsis (OR = 2.11, 95% CI: 1.03, 4.32), contrast sensitivity (OR = 2.12, 95% CI: 1.05, 4.30) and visual field defects (OR = 3.40, 95% CI: 1.69, 6.86). Conclusion: impaired visual acuity, stereopsis, contrast sensitivity and visual field defects are associated with an increased risk of low fragility hip fractures. We recommend that all patients aged >= 55 should have an annual ophthalmological examination that includes visual acuity, contrast sensitivity, stereopsis and visual field testing to assess the risks for falls and low fragility fractures.